Adult Suicide-Related emergency department encounters during the COVID-19 Pandemic: a Cross-Sectional study - Kathryn K. Ridout; Mubarika Alavi; Samuel J. Ridout; Maria T. Koshy; Sameer Awsare; Brooke Harris; David R. Vinson; Constance M. Weisner; Stacy Sterling; Esti Iturralde (The Lancet Regional Health. Americas, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic resulted in widespread psychosocial disruption, which may impact suicidal thoughts and behaviours. This study characterizes adult suicide-related emergency department (ED) encounters and patient characteristics during the COVID-19 pandemic in 2020 compared to the year prior.Methods: Retrospective cross-sectional study in a large, integrated, community-based health system of adults (≥18-years-old) with suicide-related ED encounters (defined by the Centres for Disease Control-recommended International Statistical Classification of Diseases [ICD-10-CM] codes) during the COVID-19 pandemic compared to the same period in 2019. Population-level incidence rate ratios (IRRs) compared suicide-related ED encounters in 2020 to 2019. Patient characteristics for the first suicide-related ED visit for each period were used to calculate percent relative change comparing 2020 to 2019.Findings: Of 10,651 suicide-related ED encounters in 2020 and 11,476 in 2019, 49.6% and 51.6% were for females and the mean age was 38±17 and 38±16 years-old, respectively. Suicide-related ED encounters significantly declined in each month of 2020 (IRR 0.71-0.91, p<.05), but were equivalent to 2019 levels June-August. Adults in 2020 were more likely to have co-occurring substance use disorders (+15•7%; 95% CI 7•0-24•4%) or have no mental health or suicide diagnosis associated with an outpatient visit in the last year (+21•1%, 95% CI: 12•5-29•6) compared to 2019.Interpretation: Adults with suicidal thoughts and behaviours during the COVID-19 pandemic in 2020 had distinct social and psychiatric characteristics compared to patients in the prior year. These findings can help inform health system responses to mental health needs.